Reengineering the Veress Needle for Laparoscopy - Dyrkacz, Richard; Armstrong, Sean (CMBES Proceedings, 2017)
The aim of this research study was to design an enhanced Veress needle that while maintaining its ability to access the peritoneum without causing vascular or organ damage, it could also achieve two further goals. The first objective was to allow for the passage of a guide wire directly through the needle without requiring dismantling of the inner dull stylet and the outer sharp cannula. The second objective was to increase the flow rate of intravenous fluid into the abdominal cavity. Four modified Veress needles were tested in this study. A thick diameter Veress needle with an outlet along the side of the tip modified the angle of the guide wire by 19.1 deg. This Veress needle also exhibited the highest flow rates of 0.416 ± 0.023 mL/sec and 1.668 ± 0.007 mL/sec with and without a drip chamber, respectively. However, this Veress needle required additional force when puncturing the epidermis of a pig belly at angles of 45 deg (64.4 ± 1.6 N) and 90 deg (117.3 ± 2.3 N).